Neonatal DNA methylation and childhood low prosocial behavior: An epigenome‐wide association meta‐analysis. Issue 4 (25th June 2021) - Luo, Mannan; Meehan, Alan J.; Walton, Esther; Röder, Stefan; Herberth, Gunda; Zenclussen, Ana C.; Cosín‐Tomás, Marta; Sunyer, Jordi; Mulder, Rosa H.; Cortes Hidalgo, Andrea P.; Bakermans‐Kranenburg, Marian J.; Felix, Janine F.; et al.
Abstract: Low prosocial behavior in childhood has been consistently linked to later psychopathology, with evidence supporting the influence of both genetic and environmental factors on its development. Although neonatal DNA methylation (DNAm) has been found to prospectively associate with a range of psychological traits in childhood, its potential role in prosocial development has yet to be investigated. This study investigated prospective associations between cord blood DNAm at birth and low prosocial behavior within and across four longitudinal birth cohorts from the Pregnancy And Childhood Epigenetics (PACE) Consortium. We examined (a) developmental trajectories of "chronic‐low" versus "typical" prosocial behavior across childhood in a case–control design ( N = 2, 095), and (b) continuous "low prosocial" scores at comparable cross‐cohort time‐points ( N = 2, 121). Meta‐analyses were performed to examine differentially methylated positions and regions. At the cohort‐specific level, three CpGs were found to associate with chronic low prosocial behavior; however, none of these associations was replicated in another cohort. Meta‐analysis revealed no epigenome‐wide significant CpGs or regions. Overall, we found no evidence for associations between DNAm patterns at birth and low prosocial behavior across childhood. Findings highlight the importance of employing multi‐cohort approaches to replicate epigenetic associations and reduce the risk of false positive discoveries.